Perception of time and mental health during COVID-19 pandemic quarantines - Camargo-Sánchez, Andrés; Vargas, Rafael (Universidad y Salud, 2022)
Introduction: COVID-19 pandemic made it necessary to implement obligatory quarantine measures in order to contain viral spreading. This situation generated lifestyle changes and diverse responses such as fear, anxiety, monotony, and uncertainty. This affected the people’s capacity to perceive time resulting in changes in mental health. Objective: Synthesize the neurological bases of the phenomenon of time perception, its importance and the scientific evidence regarding the possible alterations in the conditions of quarantine. Materials of methods: A thematic bibliographic review was carried out in Pubmed, Medline, Scopus, and Google Scholar databases. The Spanish and English keywords used were: perception of time, estimation of time, pandemic, cognition, emotional states, and mental health. Results: The concept of time perception, its neurological bases and the alterations that can be generated are described. Conclusions: Mental health was affected during pandemic, yet its effects in the short-term and long-term are not understood clearly.